2015
DOI: 10.1371/journal.pcbi.1004581
|View full text |Cite
|
Sign up to set email alerts
|

Neural Sequence Generation Using Spatiotemporal Patterns of Inhibition

Abstract: Stereotyped sequences of neural activity are thought to underlie reproducible behaviors and cognitive processes ranging from memory recall to arm movement. One of the most prominent theoretical models of neural sequence generation is the synfire chain, in which pulses of synchronized spiking activity propagate robustly along a chain of cells connected by highly redundant feedforward excitation. But recent experimental observations in the avian song production pathway during song generation have shown excitator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 42 publications
(70 reference statements)
1
32
0
Order By: Relevance
“…Local blockade of inhibition releases the sparse firing cells from inhibition and they begin to fire at multiple times in song 17 . Building on these observations, a recent modeling study suggested that inhibitory interneuron dynamics can increase the robustness of HVC dynamics to added noise 35 . These models can be made more precise in future experiments as additional cell-type specific information is measured.…”
Section: Discussionmentioning
confidence: 97%
“…Local blockade of inhibition releases the sparse firing cells from inhibition and they begin to fire at multiple times in song 17 . Building on these observations, a recent modeling study suggested that inhibitory interneuron dynamics can increase the robustness of HVC dynamics to added noise 35 . These models can be made more precise in future experiments as additional cell-type specific information is measured.…”
Section: Discussionmentioning
confidence: 97%
“…However, there are also clues that HVC does not contain all the information required to select a phrase transition -since more neurons correlate to the sequence's past than to its future it is possible that sequence information in HVC is lost, as expected from stochastic transitions. The source of residual stochasticity in HVC could be intrinsic to the dynamics of HVC -for example the "noise" terms commonly added in sequence generating models 13,38,39 or may enter downstream as well documented noise sources in the basal ganglia also converge on pre-motor cortical areas downstream of HVC. These early findings require further investigation of the neural dynamics during flexible transitions and may provide a tractable model for studying stochastic cognitive functions -mechanisms in working memory and sensory-motor integration that remain extremely challenging to quantify in most spontaneous behaviors in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with previous models. A large body of work has explored the generation and development of sequential activity in network models (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(41)(42)(43). While many of these models focus on the reproduction of temporally sparse synfire chain activity, few address the growing number of observations that (outside of specialized neural systems such as Nucleus HVC) sequences are rarely consistent with such a simplified description.…”
Section: Discussionmentioning
confidence: 99%
“…In Nucleus HVC of zebra finch, highly-precise sequential activity is present during song production, where many neurons fire only a single short burst during a syllable (9). In primate motor cortex, single neurons are typically active throughout a whole reach movement, but with heterogeneous and rich dynamics (10).Numerous models have explored how networks with specific synaptic connectivity can generate sequential activity (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These models span a wide range of single neuron models, from binary to spiking, and a wide range of synaptic connectivities.…”
mentioning
confidence: 99%